Om tonal analys av nutida populärmusik - Björnberg, Alf (Danish Yearbook of Musicology, 1997)
On tonal analysis of contemporary popular styles The article discusses issues related to the analysis of pitch-structures in recent popular music styles. The epistemological status of musical analysis is explained on the basis of the relationship between analysis and musical production, and it is argued that as of a consequence of this relationship, musical analysis has tended to emphasise musical syntax at the expense of matters of musical semantics. Within musicological studies of popular music, an analytical approach based on concepts from modal theory has evolved into something of a methodological mainstream. The potentials and problems of this approach are discussed in general terms, and then illustrated by way of application to three recent examples of „sidestream“ popular music. The first of these, Napalm Death’s „Suffer the children“, features a consistent modality which however transcends the modal categories identified by established modal theory. In the second example, DJ Seduction’s „Hardcore heaven“, several modes are juxtaposed to the effect of neutralising the affective character of each of these modes. The third example, Public Enemy’s „Shut em down“, features an ambiguous combination of two different modes, where the conflict between different modal tendencies serves to affectively enhance the content of the song’s lyrics. In the concluding section of the article, the discrepancy between the breaking of established musical codes in the domains of melody and harmony and the retention of conventional popular music formal models is discussed, and some possible directions for future research are suggested.